Analisis dan Uji Eksperimen Kuat Lentur Balok Kayu Meranti dan Kayu Wadang Kabupaten Malang dengan Metode Laminasi - Nono , Hendrikus Balsano; Wijaya , Handika Setya; Yurnalisdel, Yurnalisdel (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The larger the local area, the more naturally wood is available as a construction material. Compared to other basic materials, wood is a lightweight material suitable for use with simple hardware. Wood can be used in construction. Flexural strength is a type of shaft that requires considerable consideration. The purpose of this study is to determine specifically the real properties, mechanical properties, and flexural strength of plywood (glulam), in meranti wood and wadang wood, which comes from the Malang Regime. Explicit gravity testing, flexural strength, and moisture content were all conducted. Glulam radiation was tested using Epoxy and Crona sticks. The analysis results show that meranti wood and wadang wood have typical air contents of 18% and 19% respectively and typical thicknesses of 0.69 (Ton/m3) and 0.37 (Ton/m3) respectively. Based on laboratory results, the typical thick flexural strength of meranti and wadang timber perfect beams is 61.72 MPa and 38.96 MPa. In meranti wood and wadang wood, the covering layer made with paste and glue with pegs usually has a flexural strength of 22.16 MPa and 24.16 MPa, respectively.